Exploring the potentials of automation in logistics and supply chain management: Paving the way for autonomous supply chains - Benjamin Nitsche (Logistics, 2021)
The world of logistics is changing and entering a new era. The advance of digitalization and technologization enables new business models, increased process efficiencies, novel planning approaches, and much more but, on the downside, there is also the risk of being lost in the maelstrom of developments. Within these developments, the automation of logistics processes and ultimately the design of autonomous logistics systems is one of the most defining trends that has far-reaching consequences for the planning and execution of future logistics processes. This Special Issue aims to contribute to the discussion and to get to the bottom of the question of how the path towards automated and autonomous logistics systems should be designed. This editorial lays a foundation by presenting application areas of automation and discussing the theoretical path towards autonomous logistics systems. The articles that follow provide highly practical insights into current research results on the automation and autonomization of informational and physical logistics processes.
Keywords: 650; autonomous driving; autonomous logistics systems; cobots; digital twin; digitalization; industry 4.0; internet of things; logistics 4.0; process automation